IMPLEMENTATION OF INTEGRATED ASN MANAGEMENT E-GOVERNMENT SYSTEM (SIMASTEN) AT THE BANTEN PROVINCE TOURISM OFFICE TO IMPROVE ASN MANAGEMENT EFFICIENCY AND EFFECTIVENESS - Lily Irawati; Jumanah Jumanah (ASIAN PUBLISHER, 2026)
This research aims to analyze the implementation of e-government through the Integrated ASN Management System (SIMASTEN) at the Banten Province Tourism Office in improving the efficiency and effectiveness of Civil Servant (ASN) management. In the era of the Fourth Industrial Revolution, digital transformation in government administration has become a necessity. SIMASTEN is present as a digital solution that integrates various personnel services into a single integrated platform, replacing the manual system which is considered slow, inefficient, and prone to errors. This research uses a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Informants were selected through purposive sampling, involving 10 informants from leadership, technical staff, and system users. Data analysis used the interactive model of Miles, Huberman, and Saldana. The research results show that the implementation of SIMASTEN successfully improved efficiency in the dimensions of time, procedures, and personnel administration costs. From the aspect of effectiveness, SIMASTEN is able to support the achievement of organizational goals, improve data integration between work units, although the adaptation process of ASN to the system still requires assistance, especially for senior employees. This study concludes that SIMASTEN provides a significantly positive contribution to the digital bureaucratic reform in the Banten Provincial Government.